Efektivitas Bisnis Berbasis Teknologi Internet Dalam Membangun Kinerja Kewirausahaan - Mohamad Nur Utomo (BISMA (Bisnis dan Manajemen), 2019)
Entrepreneurial success will have an impact on economic growth.  Entrepreneurship that integrates internet technology in its business activities will be able to improve business performance in the current digital economy era.  This study aims to empirically examine the effect of internet technology-based business implementation on business performance.  Internet technology-based business applications are measured by 5 indicators (online communication channels, online promotion channels, online supplier distribution channels, online sales channels, and online transaction channels). While business performance is measured by 5 indicators (profit growth, sales growth, capital growth, efficiency, and customer growth).  The sample in this study was 100 UMKM in Tarakan city using the sample area probability sample method based on the sub-district area.  Data analysis technique uses PLS-SEM method with WarpPls 6.0 application.  The results showed that internet technology-based business implementation was able to encourage business performance improvement. The entrepreneur must be able to integrate its business operations with Internet-based technologies to create opportunities and facilitate building performance.Keywords: Entrepreneurship, Internet Technology, Online Business.